Fishes of the Scorpionfish subfamily Choridactylinae from the Western Pacific and the Indian Ocean - Eschmeyer, N. M.; Rama-Rao, K. V.; Hallacher, L. E. (Proceedings of the California Academy of Sciences. Fourth Series. Vol.XLI, 1979)
The Indo-Pacific scorpionfish subfamily Choridactylinae Kaup contains two genera and 10 species. The subfamily synonyms include Pelorinae Gill and Inimicinae Gill, the latter being the subfamily name applied to this group until now. Two species, with three free lower pectoral rays, are placed in the genus Choridactylus Richardson, which includes the nominal genera Chorismodactylus Gunther and Choridactylodes Gilchrist. Eight species, with two free lower pectoral rays, are included in Inimicus. Three species groups are recognized in Inimicus: (1) I. filamentosus (Cuvier); (2) I. caledonicus (Sauvage), I. japonicus (Cuvier), and I. joubini (Chevey). Nine other nominal species are recognized as synonyms, including I. bifilis Fowler and I. cirrhosus McKay. Salient features used in the descriptions of species and separation of species groups include fin-ray counts, elevation of the orbits, head shape, height of interspinous membranes, and color pattern on the inside of the pectoral fin. Descriptions and figures are provided for all species. The subfamily is distributed throughout the Indian Ocean and the Western Pacific to Japan, the major islands of the Indo-Australian Archipelago to tropical Australia, and east to Melanesia. The species are bottom-dwelling fishes of silty and sandy substrates. They are nearshore or slightly offshore forms, most occurring shallower than 40 m. Certain morphological and behavioral features allow burying in the substrate, and these features are discussed and illustrated based on aquarium observations.